Religion, human capital investments and the family in the United States - Evelyn Lilian Lehrer (Institute for the Study of Labor (IZA), 2009)
This paper critically reviews what is known, based on analyses of micro-level U.S. data, about the role of religion in various interrelated decisions that people make over the life cycle, including investments in secular human capital, cohabitation, marriage, divorce, family size and employment. It also identifies gaps in our knowledge, and suggests agenda items for future research in the field. These include use of statistical models that allow for non-linearities in the effects associated with religious participation; consideration of contextual effects; and analyses that address anomalies found in earlier work regarding patterns of non-marital sex and divorce among conservative Protestants. Further work is also needed to increase our understanding of the role that religious factors are playing as various dimensions of the second demographic transition, along with elements of American exceptionalism, continue to unfold in the U.S.
urn:nbn:de:101:1-2009082119
Keywords: J1; J2; 330; Religion; religiosity; Religion; Bildungsinvestition; Familienökonomik; Familiensoziologie; USA